Radiation shielding, dose rate and stopping power of cadmium - bismuth - lead - zinc - borate glass system: Influence of Bi2O3 doping - H. Aboud; I. T. Al-Alawy (Ядерна фізика та енергетика)
Glass systems of the form (70-x)B2O3-10ZnO-10PbO-10CdO-xBi2O3 (with x = 0 to 20 mol%) were prepared by the standard melt-quenching approach and characterized. The role of varying Bi2O3 doping contents on the radiation shielding, dose rate, and stopping power of the proposed glasses was examined. Various radiation shielding properties, such as exposure buildup factors, gamma-ray constants and dose rates, and total neutron removal cross-section, were estimated. The x-ray diffractometer patterns of the samples showed their amorphous characteristics. Glass density was increased from 5.34 to 6.95 g/cm3, and the energy band gap was reduced with the increase in Bi2O3 doping contents. In addition, both mass attenuation numbers and effective atomic numbers of the samples (calculated using Phy-X software) in the gamma-ray energy range of 0.015 to 15 MeV were increased with the increase in Bi2O3 contents. With the increase in Bi2O3 doping, the gamma-ray shielding, stopping power, and neutron removal cross-section of the glasses were improved. This new glass composition was asserted to be a good candidate for radiation shielding applications.